INTERACTIVE LEARNING USING GEOGEBRA SOFTWARE TO INCREASE MOTIVATION OF NATIVE PAPUAN STUDENTS IN LEARNING MATHEMATICS - Teguh Santoso; Deni Yuliani; Khusnul Arisma (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2024)
Papua students are still less motivated to take mathematics lessons. Students feel that mathematics is difficult and boring, so they are less interested during the mathematics learning process. The aim of this research is to increase the learning motivation of native Papuan students towards mathematics subjects using Geogebra software. The method in this research is classroom action research. This research will be carried out at SMA N 1 Warmare. The subjects used in this research were native Papuan students in class X at SMA N 1 Warmare. Data collection methods in this research include observation, questionnaire and documentation methods. The data analysis technique in this research uses descriptive analysis, namely qualitative data from observations and quantitative data from the results of the mathematics learning motivation questionnaire. In the pre-cycle, students' motivation towards mathematics was still weak on average, then in cycle 1 students' motivation to learn mathematics increased with an average of strong category, but there were still some students who had sufficient and weak motivation towards mathematics, this was shown with still the lowest score of students in the weak category. In cycle 2 there was a fairly high increase in student learning motivation, with the majority of students having a very high category, this was proven by the fact that there were no students who had weak motivation to learn mathematics. Students have also been active in participating in the learning process. Learning using Geogebra software can increase the motivation of native Papuan students in learning mathematics